Signal detection and safety analysis of three tyrosine kinase inhibitors for HER-2 positive breast cancer: a retrospective study based on the FAERS database - Xiting Tang; Chengliang Wang; Yanwei Li; Jing Tang; Guoping Zhang; Li Chen; Li Chen; Li Chen (Frontiers in Pharmacology)
ObjectiveTo identify adverse event (ADE) signals of three tyrosine kinase inhibitors (TKIs) (Tucatinib, Lapatinib, and Neratinib) used for HER-2 positive breast cancer by utilizing the FAERS database, and to analyze their safety profiles to provide references for clinical risk management.MethodsData from the FAERS database spanning Q1 2015 to Q3 2024 were retrieved, including reports where Tucatinib, Lapatinib, or Neratinib was identified as the primary suspect drug. Disproportionality analysis (ROR, PRR) and the Comprehensive Standard method were employed to detect potential ADE signals. The distribution of ADEs across different System Organ Classifications (SOCs) was also analyzed.ResultsA total of 7,848 ADE reports were analyzed, identifying 557 significant signals. The primary ADEs were concentrated in gastrointestinal disorders, general conditions, administration site reactions, and skin and subcutaneous tissue disorders. Neratinib exhibited higher gastrointestinal toxicity, Lapatinib was associated with notable skin toxicities, and Tucatinib showed specific adverse reactions linked to combination therapies.ConclusionThe three TKIs demonstrated distinct ADE signal profiles, with gastrointestinal, systemic, and skin toxicities being the major areas of concern. Future research should validate these findings and develop effective management strategies to enhance treatment safety and improve the quality of life for HER-2 positive breast cancer patients.